Inducible class C beta-lactamases produced by psychrophilic bacteria - PIERRARD A.; LEDENT P.; DOCQUIER J. D.; FELLER G.; GERDAY C.; FRÈRE J. M. (FEMS Microbiology Letters, 1998)
Only class C beta-lactamases were found to be synthesised by ampicillin-resistant psychrophilic bacteria collected in the Antarctic. Most of them were inducible but the induction factor varied greatly. Even in non-induced conditions, where no lysis occurred, a large proportion of the activity was found in the culture supernatant, an unusual observation with class C producers. (C) 1998 Federation of European Microbiological Societies. Published by Elsevier Science B.V.